Yes, you can, in fact, reuse your leeches without the fear of nosocomial infections - Soula, Mariajesus (Kansas State University, 2024)
Introduction: Leeches are used in human and veterinary medicine as a treatment for venous congestion. It is recommended to discard leeches after one use. A concern with reusing leeches is potential spread of bacterial infections. If a leech were to harbor bacteria from one patient in its gastrointestinal (GI) tract, it may transmit them to another patient, potentially, even serving as a vector for multidrug resistant (MDR) infection. We sought to determine the safety of reusing leeches inoculated with an MDR Staphylococcus aureus. Study design: Experimental, ex-vivo Animals: 63 leeches were split into eight treatment groups and one control group. Methods: Treatment leeches were fed canine blood inoculated with an MDR strain of Staphylococcus aureus while control leeches were fed clean canine blood. Cultures were obtained at 1 day, 1 week, and 1-, 2-, 3- and 4-months post-inoculation. At each time point, cultures were taken of aquarium water, GI contents, and blood that the leeches were allowed to feed on. Cultures were evaluated for the presence of Staphylococcus aureus. Results: All water samples were negative except for one tank at seven days. After two months and three months, all GI tracts and blood meal samples were negative, respectively. Clinical significance: Leeches will harbor MDR Staphylococcus aureus after inoculation with infected canine blood. This bacterium is not detectable in the water after 7 days and no longer detectable in the leech or blood meal after 3 months.
Keywords: Leeches; MRSP